New optical total recursion for electromagnetic flux of optical fiber with optical microscale - Korpinar, Talat; Korpinar, Zeliha; Yeneroglu, Mustafa (Elsevier Gmbh, 2022)
In this paper, we describe optical spherical total recursion flux of optical fiber with normalized microscale in the spherical space. Also, we obtain spherical normalized microscale by the recursion operator of Lorentz force. Moreover, we construct optical spherical ferromagnetic recursion flux by using optical spherical ferromagnetic normalized microscale in spherical space. Finally, we demonstrate spherical normalized microscale with spherical ferromagnetic model.
Keywords: Spherical frame; Optical fiber; Optical spherical total recursion flux; Ferromagnetic spin; Normalized microscale